Cd2+ adsorption performance of tunnel-structured manganese oxides driven by electrochemically controlled redox. (January 2019) - Liu, Lihu; Peng, Qichuan; Qiu, Guohong; Zhu, Jun; Tan, Wenfeng; Liu, Chengshuai; Zheng, Lirong; Dang, Zhi
Abstract: The heavy metal ion adsorption performance of birnessite (a layer-structured manganese oxide) can be enhanced by decreasing the Mn average oxidation state (Mn AOS) and dissolution−recrystallization during electrochemical redox reactions. However, the electrochemical adsorption processes of heavy metal ions by tunnel-structured manganese oxides are still enigmatic. Here, tunnel-structured manganese oxides including pyrolusite (2.3 Å × 2.3 Å tunnel), cryptomelane (4.6 Å × 4.6 Å tunnel) and todorokite (6.9 Å × 6.9 Å tunnel) were synthesized, and their electrochemical adsorptions for Cd 2+ were performed through galvanostatic charge−discharge. The influence of both supporting ion species in the tunnel and tunnel size on the electrochemical adsorption performance was also studied. The adsorption capacity of tunnel-structured manganese oxides for Cd 2+ was remarkably enhanced by electrochemical redox reactions. Relative to K + in the tunnel of cryptomelane, the supporting ion H + was more favorable to the electrochemical adsorption of Cd 2+ . With increasing initial pH and specific surface area, the electrochemical adsorption capacity of cryptomelane increased. The cryptomelane electrode could be regenerated by galvanostatic charge−discharge in Na2 SO4 solution. Due to the differences in their tunnel size and supporting ion species, the tunnel-structured manganese oxides follow the order of cryptomelane (192.0 mg g −1 ) > todorokite (44.8 mg g −1 ) > pyrolusite (13.5 mg g −1 ) in their electrochemical adsorption capacities for Cd 2+ . Graphical abstract: Cd 2+ adsorption capacities of tunnel-structured manganese oxides are remarkably improved by electrochemically controlled redox reactions. Image 1 Highlights: Tunnel-structured manganese oxides are used for electrochemical adsorption of Cd 2+ . The adsorption capacity is remarkably improved by electrochemical redox reactions. The highest adsorption capacity of cryptomelane for Cd 2+ reaches 192.0 mg g −1 . The adsorption capacity follows the order of cryptomelane > todorokite > pyrolusite. Ion exchange contributes much to the electrochemical adsorption of manganese oxides. Abstract : The present study elucidates the mechanism and influencing factors of Cd 2+ adsorption by tunnel-structured manganese oxides in electrochemical redox processes.